The determinants of COVID-19 vaccine uptake among migrants from 109 countries residing in China: A cross-sectional study - Chen, Hao; Lei, Weitian; Wei, Zhengyi; Wang, Fan (Frontiers in Public Health, 2023)
Background: The present study aimed to investigate the prevalence of coronavirus disease 2019 (COVID-19) vaccine uptake among foreign migrants in China and to explore the determinants of their vaccine uptake behaviour. Methods: From June to October 2021, we used convenience and snowball sampling to recruit a sample of 764 participants from five cities in which the overwhelming majority of foreign migrants in China live. Chi-square (χ2) tests were used to examine vaccination distribution according to demographic characteristics. Multivariate logistic regression models visualized by forest plot were used to investigate the associations between significant determinants and vaccine uptake. Results: Overall, the prevalence of vaccination rate was 72·9% (95% confidence interval (CI): 69·9% 76·0%). Migrants whose social participation was very active (adjusted odds ratio (AOR): 2·95, 95%CI: 1·36-6.50, P=0·007) or had perceived COVID-19 progression prevention by the vaccine (AOR: 1·74, 95%CI: 1·01-3·02, P=0·012) had higher odds of vaccination compared to those whose social participation was inactive or who did not have this perception. Migrants who perceived the vaccine uptake process as complex (AOR: 0·47, 95%CI: 0·27-0·80, P=0·016) or were unsure of their physical suitability for the vaccine (AOR: 0·40, 95%CI: 0·24-0·68, P<0·001) had lower odds of vaccination compared to those who did not have these perceptions. Furthermore, migrants from emerging and developing Asian countries (AOR: 2·32, 95% CI: 1·07-5·21, P=0·04) and the Middle East and Central Asia (AOR: 2·19, 95% CI: 1·07-4·50, P=0·03) had higher odds of vaccination than those from major advanced economies (G7) countries, while migrants from other advanced economic countries (AOR: 0·27, 95% CI: 0·11-0·63, P=0·003) had lower odds of vaccination than those from G7 countries. . Conclusions: It may be beneficial to promote vaccine uptake among migrants by ensuring effective community engagement, simplifying the appointment and uptake process, and advocating the benefits and target populations of the COVID-19 vaccine.